PENGARUH KEMAMPUAN SISWA MENGIDENTIFIKASI GAYA BAHASA TERHADAP KEMAMPUAN MENULIS CERITA - Simanjuntak, Harlen; Uli Lubis, Debora; Sitorus, Pontas; Pane, Januaris (Universitas Islam Sumatera Utara, 2023)
This study aims to determine the effect of students' ability to identify language styles on the ability to write inspirational stories. Factors that cause low students' writing skills are due to the lack of students' vocabulary, the difficulty of conveying ideas in writing. and less able to understand the style of language. This study used a quantitative experimental method, with class IX research subjects at SMP N 4 Laguboti T.A 2022/2023, with a total population of 194 students and a sample of 32 people. Determination of the sample using the lottery technique. This type of research design is a pre-experimental design, namely the One Group Pretest-Posttest design which only uses one class for learning. The data collection technique is to give test assignments to students. The results of this study indicate that the activity of identifying language style influences the ability to write inspirational stories, this is evident from the Hypothesis Test which has been carried out with Fcount Ftable or 11.59 2.03. So that Ho is rejected and Ha is accepted.